Boda bodas rule: Non-agricultural activities and their inequality implications in Western Kenya - Jann Lay; George Michuki M'Mukaria; Toman Omar Mahmoud (Kiel Institute for the World Economy (IfW), 2007)
Engagement in non-agricultural activities in rural areas can be classified into survival-led or opportunity-led. Survival-led diversification would decrease inequality by increasing the incomes of poorer households and thus reduce poverty. By contrast, opportunity-led diversification would increase inequality and have a minor effect on poverty, as it tends to be confined to non-poor households. Using data from Western Kenya, we confirm the existence of the differently motivated diversification strategies. Yet, the poverty and inequality implications differ somewhat from our expectations. Our findings indicate that in addition to asset constraints, rural households also face limited or relatively risky high-return opportunities outside agriculture.
Keywords: Q12; O17; I31; 330; Non-agricultural activities; Poverty; Sub-Saharan Africa; Kenya; Inequality; Income diversification; Dorfwirtschaft; Landwirtschaftlicher Kleinbetrieb; Diversifikation; Ländliches Einkommen; Einkommensverteilung; Kenia (West); Afrika südlich der Sahara